2019
DOI: 10.1186/s40623-019-1048-0
|View full text |Cite
|
Sign up to set email alerts
|

Earth atmospheric loss through the plasma mantle and its dependence on solar wind parameters

Abstract: Atmospheric loss and ion outflow play an important role in the magnetospheric dynamics and in the evolution of the atmosphere on geological timescales-an evolution which is also dependent on the solar activity. In this paper, we investigate the total O + outflow [ s −1 ] through the plasma mantle and its dependency on several solar wind parameters. The oxygen ion data come from the CODIF instrument on board the spacecraft Cluster 4 and solar wind data from the OMNIWeb database for a period of 5 years (2001-200… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
41
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
3

Relationship

4
3

Authors

Journals

citations
Cited by 30 publications
(47 citation statements)
references
References 73 publications
4
41
2
Order By: Relevance
“…The outflowing flux ratio between O + and H + (F O /F H ) is about 0.1 for suprathermal energy range (thermal ion instrument for < 50 eV) and is close to 1 for hot ion energy range of > few eV up to tens keV (Moore et al, 1999;Curry et al, 2003;Peterson et al, 2001;Sandhu et al, 2016). Similar difference is also found on the solar EUV effect (not solar zenith angle but F10.7) between the suprathermal ion observation by Akebono (Cully et al, 2003) and the hot ion observation by Cluster (Schillings et al, 2019). The former showed more than one order magnitude increase of outflow flux for O + with very little increase for H + .…”
Section: Suprathermal and Hot Outflowssupporting
confidence: 59%
See 1 more Smart Citation
“…The outflowing flux ratio between O + and H + (F O /F H ) is about 0.1 for suprathermal energy range (thermal ion instrument for < 50 eV) and is close to 1 for hot ion energy range of > few eV up to tens keV (Moore et al, 1999;Curry et al, 2003;Peterson et al, 2001;Sandhu et al, 2016). Similar difference is also found on the solar EUV effect (not solar zenith angle but F10.7) between the suprathermal ion observation by Akebono (Cully et al, 2003) and the hot ion observation by Cluster (Schillings et al, 2019). The former showed more than one order magnitude increase of outflow flux for O + with very little increase for H + .…”
Section: Suprathermal and Hot Outflowssupporting
confidence: 59%
“…These observations indicate that the energization of the dayside hot ion outflow at mid-and high-altitudes are mainly by waves or other non-thermal processes (Moore et al, 1999;Lennartsson et al, 2004;Waara et al, 2011). This applies even at ions is plotted as a function of the solar wind dynamic pressure for different IMF clock angle (CA), which is defined as 0 • for northward IMF (Schillings et al, 2019) low-altitudes because majority of the dayside outflowing ions at low altitudes are conic-like at low altitude rather than beam like (Norqvist et al, 1996;Peterson et al, 2008). On the other hand, a substantial part of nightside outflow is in the beam form (Norqvist et al, 1998;Peterson et al, 2008), after most likely accelerated by parallel electric potential above the discrete aurora.…”
Section: Suprathermal and Hot Outflowsmentioning
confidence: 77%
“…(1) cold ion that will end up mainly in the plasma sheet (Mouikis et al, 2010;Haaland et al, 2012;Liao et al, 2015), (2) energised ions from the cusp to the plasma mantle (Liao et al, 2010;Slapak et al, 2017;Schillings et al, 2019), (3) energised ions from to cusp going directly to the magnetosheath (Slapak et al, 2017). Slapak et al (2017); Slapak and Nilsson (2018); Schillings et al (2019) suggested that ions observed in the plasma mantle have sufficient energy and velocity to escape in the distant tail. However, our results show that very few ions reach the distant tail but instead escape directly through the magnetopause after a few minutes (∼ 22 min).…”
Section: Discussionmentioning
confidence: 99%
“…Based on previous suggestions that O + ions from the plasma mantle are escaping (Slapak et al, 2017;Slapak and Nilsson, 2018;Schillings et al, 2019), we investigate the fate of ions by tracing the particles forward in time in the magnetospshere.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation